Improving E-Commerce Website Rank Using Search Engine Optimization (SEO) - Asrigo, Riki; Kaburuan, Emil R. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Search engine optimization (SEO) plays an important role in increasing website visibility with keywords that users want. The aimed of this study is pertains to optimizing a website, to improve the rank and get a better position for web pages in the search engine results page (SERP). Applying SEO is expected to increase traffic that can boost sales figures. This paper adopts Jamal-Hatab’s SEO framework as research base. The framework contains a set of guidelines, namely keywords analysis, submit sites URL to search engines directories, optimize website SEO Factors, and measure results. Target of this study is e-commerce website in Country of Indonesia with monthly average of 758 visitors and rank position 53 million by Ahref before optimization. The finding describes the website as having a low page rank and number of visitors. The optimizing results will measure every week, verifying the framework in improving website rank, page position in Google SERPs, increase traffic and visitor of the website at Google Search Engine. These goals are very important for the company to enhance its business capabilities and build the brand. As a result, SEO tasks can help boost the website rank, put webpages on the first page of SERP, and help maintain the position, but not in increasing visitors and traffics. More time, and continues optimization such as add keywords, make the website mobile friendly, and getting more social media support is highly suggested.